MALAYSIAN YOUTH EXPECTATIONS OF SOCIAL MEDIA INFLUENCERS (SMI) (Journal of Creative Industry and Sustainable Culture, 2022)
The use of social medias has become more common now than before. Attachment to social medias has led to the rise of a new kind of ‘celebrity’ known as Social Media Influencer (SMI). The study aims to gain a better understanding of what the Malaysian youth expects from the SMIs. In particular, it explores the attributes of SMIs that attract followers and the underlying benefits sought after by them. Data for the study is collected using semi-structured interviews with 31 participants. Soft laddering technique was used to increase depth into the data which is then analyzed using means-end approach and presented in the form of hierarchical value map (HVM). The findings suggest that the consumption experiences of following and interacting with SMIs are mainly intrinsic and hedonic. Malaysian youth generally follow social media influencers who are genuine, knowledgeable, motivational, relatable, and creative. The values gained from following social media influencers are mainly positive values such as trust, personal development, positivity, confidence, inspiration, knowledge, and personal well-being.